2011
DOI: 10.1002/ana.22435
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome‐associated MEIS1 risk variant influences iron homeostasis

Abstract: Restless legs syndrome (RLS) is a frequent sleep disorder that is linked to disturbed iron homeostasis. Genetic studies identified MEIS1 as an RLS-predisposing gene, where the RLS risk haplotype is associated with decreased MEIS1 mRNA and protein expression. We show here that RNA interference treatment of the MEIS1 worm orthologue increases ferritin expression in Caenorhabditis elegans and that the RLS-associated haplotype leads to increased expression of ferritin and DMT1 in RLS brain tissues. Additionally, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 27 publications
7
64
0
1
Order By: Relevance
“…In a set of altogether 3447 KORA individuals, none of these SNPs were associated with serum iron or any of the iron-related parameters in serum (ferritin, transferrin, transferring saturation, and soluble transferrin receptor; see Supplementary Table 3 for association results). In view of a recent report of Catoire et al, 21 we further tested whether the risk haplotype of the RLS gene MEIS1 (G alleles of rs12469063 and rs2300478) is associated with any serum iron parameter. This test also gave a negative result with no P-value being smaller than 0.45 (KORA F3)/0.27 (KORA F4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a set of altogether 3447 KORA individuals, none of these SNPs were associated with serum iron or any of the iron-related parameters in serum (ferritin, transferrin, transferring saturation, and soluble transferrin receptor; see Supplementary Table 3 for association results). In view of a recent report of Catoire et al, 21 we further tested whether the risk haplotype of the RLS gene MEIS1 (G alleles of rs12469063 and rs2300478) is associated with any serum iron parameter. This test also gave a negative result with no P-value being smaller than 0.45 (KORA F3)/0.27 (KORA F4).…”
Section: Resultsmentioning
confidence: 99%
“…Again, this failure may be due to a 'dilution' phenomenon analogous to the one explained above. Recently, Catoire et al 21 reported that in RLS patients the risk haplotype of the RLS gene MEIS1 is associated with increased thalamic ferritin expression, whereas the expression in another cerebral tissue (pons) or in lymphoblastoid cell lines did not depend on that haplotype. Data on liver expression and data on the general population were not provided but may be desirable in view of the fact that we could not detect an association between this haplotype and serum ferritin in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…32 The idea of allele-dependent epigenetic effects for iron finds further support in evidence that iron-deficient conditions reduce MEIS1 expression in cultured human cells. 28 Temporal dissociation of RLS sensory symptoms from its motor signs (eg, in PLMs that can reflect an asymptomatic forme fruste of RLS and that are affected by some of the same genetic factors) is also problematic. Therefore, further knowledge of the genetic architecture of RLS will demand comprehensive phenotyping that includes asymptomatic individuals with PLMs.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…An additional confounder is the potential for tissue-specific regulation of genes implicated in RLS, as has been suggested for MEIS1. 28 Increased comorbidity of RLS-like symptoms with other medical conditions represents either an opportunity to identify biological factors that influence trait expressivity by way of the at-risk alleles or problematic phenocopies. For example, RLS/PLMs are exceedingly common in endstage renal disease, 3 and are associated with BTBD9 and MEIS1 variants in northern Europeans, 33 and PTPRD variants in Taiwanese people 34 ; however, these associations are not discernible in patients with multiple sclerosis experiencing RLS-like symptoms.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…Genomewide association studies in humans have revealed PTPRD as a risk factor for restless legs syndrome (RLS) (57,74); however, the mechanism accounting for its role in RLS is currently unknown. One of the pathological characteristics of RLS is low iron content in the substantia nigra, and a significant percentage of patients with RLS are responsive to iron treatment (9,13,66). The single nucleotide polymorphism (SNP) density near Ptprd in BXD RI mice is high (3,476), thereby making it a good candidate underlying individual differences in iron regulation.…”
Section: Principal Components Analysis and Candidate Genesmentioning
confidence: 99%